Long term recovery of IgG and IgM production during HIV infection in a patient with common variable immunodeficiency (CVID). Issue 9 (1st September 2001) - Jolles, S; Tyrer, M; Johnson, M; Webster, D
Abstract : Aims —Common variable immunodeficiency (CVID) is the most common serious primary immunodeficiency. This paper describes the immunological consequences of human immunodeficiency virus (HIV) infection in a patient with familial CVID subsequently treated with highly active antiretroviral therapy (HAART). Methods —Serial measurements over 11 years of serum immunoglobulins, specific antibodies to tetanus toxoid and pneumococcal polysaccharides, lymphocyte phenotypes, and HIV viral load were made. Results —The patient recovered total serum IgG and IgM, but not IgA production, with adequate concentrations of specific antibodies, allowing withdrawal of intravenous immunoglobulin without an increase in infections. T cell numbers gradually declined and the patient developed a high grade B cell lymphoma. After successful chemotherapy, HAART was commenced, viral load fell from 472 000 to < 50 copies/ml, and CD4 + T cell numbers increased from 13 to 661 × 10 6 /litre. Antibody production was maintained after suppression of viral load. Conclusions —This is the first definitive report of reversal of IgG and IgM deficiency in familial CVID after HIV infection. Failure to normalise IgA supports the concept of separate predisposing genetic factors for selective IgA deficiency, which when combined with others lead to CVID. Furthermore, a persistently high viraemia is not required to maintain the recovery of immunoglobulin values, suggesting this depends either on a transitory effect of a high viral load, or a persistence of low amounts of virus.